2017
DOI: 10.1007/s00246-016-1549-6
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Magnetic Resonance Feature Tracking Biventricular Two-Dimensional and Three-Dimensional Strains to Evaluate Ventricular Function in Children After Repaired Tetralogy of Fallot as Compared with Healthy Children

Abstract: Cardiac magnetic resonance imaging is an important tool to evaluate cardiac anatomy and ventricular size and function after repaired tetralogy of Fallot. Magnetic resonance tissue tagging is the gold standard for evaluation of myocardial strain. However, myocardial tagging strain requires tagged images to be obtained prospectively, during the scan and with limited temporal resolution. Cardiac magnetic resonance feature tracking is a new tool that allows the retrospective analysis of cine images. There is limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…This difference between 2D and 3D regional strain needs to be investigated further in a patient group. Berganza et al reported that the 3D GCS was associated with the indexed right ventricular EDV in patients with repaired tetralogy of Fallot [12]. We found a strong correlation between 3D GCS and indexed EDV, indexed ESV, EF in the Fontan repair patients.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…This difference between 2D and 3D regional strain needs to be investigated further in a patient group. Berganza et al reported that the 3D GCS was associated with the indexed right ventricular EDV in patients with repaired tetralogy of Fallot [12]. We found a strong correlation between 3D GCS and indexed EDV, indexed ESV, EF in the Fontan repair patients.…”
Section: Discussionsupporting
confidence: 65%
“…3D strain clinical research had been reported in recent years [21]. Considering the difficulties in ventricular function assessment in Fontan FSV repair patients due to the complex ventricular geometry, 3D strain analysis by FT may be a more accurate tool than 2D strain analysis [12]. In a study of 100 healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…been used to analyze ventricular function in CHD, particularly in cases of coarctation of the aorta [18] and repaired transposition of the great arteries [19]. Considering the difficulties in ventricular function assessment in Fontan FSV repair patients due to the complex ventricular geometry, 3D strain analysis by FT may be a more accurate tool than 2D strain analysis [12]. In a study of 100 healthy subjects.…”
Section: Cmr-ft Is a Non-invasive Modality For Evaluating Ventricularmentioning
confidence: 99%
“…However, ventricular function assessment is challenging in post-Fontan FSV patients due to the complex ventricular geometry. Some studies have indicated that three-dimensional (3D) strain analysis may overcome such geometry-dependent limitations of 2D strain analysis by referencing the intrinsic directions of deformation [12,13]. To our knowledge, there are no previous studies assessing three-dimensional strain analysis of SSFP cine images in Fontan patients and normal volunteers [14].…”
Section: Introductionmentioning
confidence: 99%